1997
DOI: 10.1093/clinchem/43.6.976
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I, cardiac troponin T, and creatine kinase MB in dialysis patients without ischemic heart disease: evidence of cardiac troponin T expression in skeletal muscle

Abstract: Serum cardiac troponin T (cTnT) concentrations are frequently increased in chronic dialysis patients as measured by the first-generation ELISA immunoassay, as is creatine kinase (CK) MB mass in the absence of acute ischemic heart disease. We designed this study to compare four serum markers of myocardial injury [CK-MB mass, first-generation ELISA cTnT, second-generation Enzymun cTnT, and cardiac troponin I (cTnI)] in dialysis patients without acute ischemic heart disease. We also evaluated skeletal muscle from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(76 citation statements)
references
References 28 publications
1
73
0
2
Order By: Relevance
“…Cardiac troponin I is specific for detection of myocardial injury in chronic renal failure as opposed to creatinine kinase enzyme levels. [12][13][14] Elevated troponin levels independently predicted increased left ventricular mass and systolic dysfunction in patients with CKD [15][16][17] with high positive predictive values for left ventricular hypertrophy and high negative predictive values for systolic dysfunction. [16][17][18] All patients in group 2 had ventricular hypertrophy, systolic dysfunction, and continued elevation of troponin I levels at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponin I is specific for detection of myocardial injury in chronic renal failure as opposed to creatinine kinase enzyme levels. [12][13][14] Elevated troponin levels independently predicted increased left ventricular mass and systolic dysfunction in patients with CKD [15][16][17] with high positive predictive values for left ventricular hypertrophy and high negative predictive values for systolic dysfunction. [16][17][18] All patients in group 2 had ventricular hypertrophy, systolic dysfunction, and continued elevation of troponin I levels at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed no correlation between elevated troponins and serum creatinine or BUN, which is in agreement with previous studies. 2,7,12 Since the kidney is unlikely to be responsible for the troponin clearance, it is impossible that the decreased clearance of troponin is responsible for the elevations. 9 Re-expression of the cardiac isoform of cTnT in myopathic skeletal muscle of patients with ESRD is controversial.…”
Section: Causes Of Troponin Elevations In End-stage Renal Diseasementioning
confidence: 99%
“…9 Re-expression of the cardiac isoform of cTnT in myopathic skeletal muscle of patients with ESRD is controversial. 7,8,18 Cross reactivity with skeletal muscle is unlikely, since the troponin T assay has been refined; cross reaction with skeletal muscle is not a problem with the second-and third-generation assays. 18 Troponin elevation may be due to repeated episodes of clinically silent, small MIs 8, 9 because CAD is common in these patients.…”
Section: Causes Of Troponin Elevations In End-stage Renal Diseasementioning
confidence: 99%
See 2 more Smart Citations